The development of hybridized competency-based teacher candidate selection system - Ramli, Razamin; Ghazali, Mohd Izam; Ibrahim, Haslinda; Mat Kasim, Maznah; Mohmad Kamal, Fazillah (Universiti Utara Malaysia, 2012)
Teachers form the backbone of any educational system, hence selecting the most qualified candidate is very crucial.The teacher candidate-selection for any teacher training program is an important decision making process that must be carried out carefully.The decision making process involves a couple of stages: the entry exam and the interview session. It is a difficult process due to the increasing demand and expectation towards teacher in society.Furthermore, selecting capable and suitable candidates from a pool of applicants is becoming a more complicated and difficult task since the society’s and nation’s preferences need to be satisfied as much as possible. Teacher candidates’ selection highly depends on human judgment especially during interview session. In this study, an efficient and multi-criteria teacher- candidate selection model for the interview session was developed. Initially, the related teacher-candidate selection criteria were determined based on expert input that is those who are involved in interviewing teacher-candidate from a public university.The proposed three main criteria are content of knowledge, communication skills and personality. Furthermore, each main criteria was divided into a few sub-criteria.The Analytical Hierarchy Process (AHP) technique was employed to allocate weight for the criteria and later a Simple Weighted Average (SWA) approach was used to develop a model.The proposed model may assist on selecting most qualified teacher candidates. In order to implement the multi-criteria selection model, a web-based Decision Support System was developed. This system which is called as Teacher-Candidate Selection (TeCaS) is expected to assist the interviewer panel during the selection process.